Arrange these numbers from least to greatest: -5/8, -7/9, -4/5, -3/7 A. -7/9 -5/8 -3/7 -4/5
B. -4/5 -7/9 -5/8 -3/7
C. -4/5 -5/8 -7/9 -3/7
D. -3/7 -4/5 -5/8 -7/9

Answers

Answer 1
Answer: for this question, the easiest way is to find the decimal for each fraction. 
so you can say: 
-5/8 = -0.6 
-7/9 = -0.7 
-4/5 = -0.8 
-3/7 - -0.4 
and because they are all negative numbers so from the least to the greatest will be: 
-4/5 < -7/9 < -5/8 < -3/7 
so the answer is B :)))
i hope this is helpful 
have a nice day 
Answer 2
Answer:

Answer:

b

Step-by-step explanation:

you have to find the common denominator  or turn it into a decimal


Related Questions

Sofia asked the students in her class to name Thier favorite sport. she made this list to display the results. ●1/3 of the students named basketball ● 1/8 of the students named soccer ● 5/12 of the students named football and the rest of the class named baseball. what fraction of the students named baseball as their favor to sport?. show work
Tim can mow 4 lawns in 6 hours. How many lawns can be mow in 15 hours?
Thomas ordered 2 Japanese comic books and twice that number of American comic books. He also ordered 4 Spanish comic books. Thomas told his mom he ordered 8 comic books. Was Thomas's calculation reasonable?A.Yes, it is reasonable because 2 + 2 + 4 = 8.B.No, it is not reasonable because 2 + 4 = 6.C.No, it is not reasonable because 2 + 4 + 4 = 10.
Tyrone takes 3/4 hour to paint a wall. His brother takes 1/3 of the time he takes. How long will his brother take to paint five similar wall.
What is the LCD of 1/2 and 2/17?A.1B.17C.19D.34

What is the result of the following division?

Answers

For this case we must indicate the result of the following expression:

\frac {2x ^ 3-3x + 5} {x + 3}

We must build a quotient that, when multiplied by the divisor, eliminates the terms of the dividend until it reaches the remainder.

It must be fulfilled that:

Dividend = Quotient * Divider + Remainder

Answer:

See the attached image

Option A

Answer: Choice A

Step-by-step explanation:

Write and equation in standard form for a line that is (a) parallel (b) perpendicular to the line with an equation of y= 3x - 5 that passes through the point (5,8)

Answers

Answer:

  (a) 3x -y = 7

  (b) x +3y = 29

Step-by-step explanation:

(a) The standard form of the given line is ...

  3x -y = 5

The parallel line will have a constant on the right that makes it go through (5, 8), so it will be ...

  3x -y = 3(5) -(8)

  3x -y = 7

__

(b) The perpendicular line will have coefficients for x and y swapped and one of them negated. Again, the constant is chosen to make it go through (5, 8).

  x + 3y = (5) +3(8)

  x + 3y = 29

What is the factor of 36

Answers

the square root rounded up to the nearest integer, 6.
testing the values 1 through 6 for division into 36 we find factors of 36 which are : (1, 36)
(2, 18)
(3, 12)
(4, 9)
(6,6)
or in other words the sets would be : 1, 2 , 3, 4 , 6 , 9 , 12 , 18 , 36
1 and 36), (2 and 18), (3 and 12), (4 and 9), (6 and 6) or the set 1, 2, 3, 4, 6, 9, 12, 18, 36.

the pumpkin patch is open every day if it sells 2,750 pounds of.pumpkins each day about how many pounds does it sell in 7 days

Answers

if you multiply 2,750 with 7 it will get you the amount 
which is 19250 pounds 
Multiply 2750 by 7 to get 19250. Thus, the pumpkin patch will sell 19,250 pounds of pumpkins in 7 days.

Find the measure of b.

Answers

Answer:

74°

Step-by-step explanation:

b + 16°= 90°

b = 74°

the steps to the equation

Which of the following functions best represents the graph?f(x) = x3 + x2 − 4x − 4
f(x) = x3 + 4x2 − x − 4
f(x) = x3 + 3x2 − 4x − 12
f(x) = x3 + 2x2 − 4x − 8

Answers

Answer:

f(x)=x^3+x^2-4x-4

Step-by-step explanation:

From the graph, the x-intercepts are;

x=-2

x=-1

x=2

These are root of the polynomial function represented by the given graph.

By the remainder theorem;

f(-2)=0,f(-1)=0,f(2)=0

According to the factor theorem, if (x-a) is a factor of f(x), then f(a)=0

This implies that;

(x+2),(x+1),(x-2) are factors of the required function.

Hence; f(x)=(x+1)(x-2)(x+2)

We expand using difference of two squares to obtain;

f(x)=(x+1)(x^2-4)

We expand using the distributive property to get;

f(x)=x^3-4x+x^2-4

Rewrite in standard form to obtain;

f(x)=x^3+x^2-4x-4

Answer:

Choice A: f(x) = x^3 + x^2 − 4x − 4

Step-by-step explanation:

Here's a great and simple answer.

Ok first we need to take the x intercepts to solve.

If we look at the graph we see the x ints are -2,+1 and +2.

To solve we need to put them into factor form

= (x-2) (x+2) and (x+1)

Simplify: (x-2) (x+2) = (x^2-4) and (x+1)

Now we take (x^2-4) and (x+1) and multiply them to find our answer

(x^2-4) (x+1)

= x^2(x) and x^2(1) = x^3 and x^2.

now the other: -4(x) and -4(+1) = -4x and -4

We have nothing common here so we just join them

= x^3 + x^2 - 4x - 4, and that is the same as choice A.